MYH9 disorder: Identification and a novel mutation in patients with macrothrombocytopenia. Issue 7 (15th April 2021) - Natesirinilkul, Rungrote; Sosothikul, Darintr; Komwilaisak, Patcharee; Pongtanakul, Bunchoo; Narkbunnum, Nattee; Yudhasompop, Najwa; Mekjarusgool, Pimsiri; Niparuck, Pimjai; Boonyawat, Kochawan; Kunishima, Shinji; Sirachainan, Nongnuch
Abstract: The diagnosis of MYH9 disorder is guided by recognizing granulocyte Döhle body‐like inclusion bodies and large/giant platelets in the peripheral blood smear. Immunofluorescence study of nonmuscle myosin heavy chain IIA is a sensitive screening method for diagnosis of MYH9 disorder. The diagnosis can then be confirmed by genetic analysis. A total of 67 patients with macrothrombocytopenia were included, of which 11 patients (16%), aged 4 months to 22 years, were ultimately diagnosed with MYH9 disorder. One novel mutation in exon 30 at c.4338T>C (p.F1446A) was detected. This mutation was associated with nonhematologic manifestations presenting in late adolescence with cataracts, hearing loss, and hematuria.